Teacher quality and its cultural contexts: What can the west learn from the east? - Kerry, J. Kennedy (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2011)
Research on teacher quality is derived from a Western model of education that is obsessed with student achievement. Often comparisons with student achievement in East Asian societies leave Western policymakers asking: “why aren‟t our students as good as theirs?” The answer is often that improvements in teacher quality are the key variable in enhancing student achievement and much policy effort is spent on identifying the links between the two variables. Qualifications, licensing arrangements, teacher education, salary incentives, instructional style and teacher efficacy have all been nominated as likely ingredients in this elusive construct of "teacher quality‟.